KETERAMPILAN METACOGNITIVE EXPERIENCE SISWA PADA PEMBELAJARAN MATEMATIKA DI SD NEGERI KOTALAMA 1 MALANG - Inna Megawati; Edy Bambang Irawan; Sulton Sulton (Jurnal Kajian Pembelajaran Matematika, 2017)
this research focus of describing the skill of metacognitive experience student of mathematic learning in elementary school of kotalama 1 malang. Description the skill of metacognitive experience about character for metacognitive feelings dan metacognitive judgment student. Research of procedur used is with do observation, documentation, then interview. Research for subject  what index finger that is student grade IV B as many as 5 people with character is different. Research of result acquisition that is metacognitive feelings student still not yet appear, metacognitive judgment student no happen because there is connect between metacognitive feelings with judgment. Beside it’s, feelings for student can acquisition because there is support principle of learn from around area. Method of teach by teacher so influence character for metacognitive feelings and metacognitive judgment student.